LITOSTRATIGRAFI CEKUNGAN OMBILIN BERDASARKAN INTERPRETASI CITRA SATELIT - -, Yuyun Yuniardi (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
Stratigraphy of Ombilin Basin area was interesting for make some research. The research did use remote sensing interpretation to made geological interpretation map which is containing information about lithostratigraphic unit distribution in Ombilin Basin area. LithoStratigraphic of Ombilin Basin from old to young were Brani Formation, Sangkarewang Formation, Sawahlunto Formation, Sawahtambang Formation, and Ombilin Formation.